Cortex Thickness Is Key for the Colors of Iridescent Starling Feather Barbules With a Single, Organized Melanosome Layer - Freyer, Pascal; Wilts, Bodo D.; Stavenga, Doekele G. (Frontiers in Ecology and Evolution, 2021)
The iridescent plumage of many birds is structurally coloured due to an orderly arrangement of melanosomes in their feather barbules. Here, we investigated the blue- to purple-coloured feathers of the European starling (Sturnus vulgaris) and the blue and green feathers of the Cape starling (Lamprotornis nitens). In both cases, the barbules contain essentially a single layer of melanosomes, but in S. vulgaris they are solid and rod-shaped, and in L. nitens they are hollow and rod- as well as platelet-shaped. We analysed the colouration of the feathers by applying imaging scatterometry, bifurcated-probe- and micro-spectrophotometry. The reflectance spectra of the feathers of the European starling showed multiple peaks and a distinct, single peak for the Cape starling feathers. Assuming that the barbules of the two starling species contain a simple multilayer, consisting locally only of a cortex plus a single layer of melanosomes, we interpret the experimental data by applying effective-medium-multilayer modelling. The optical modelling provides quantitative insight into the function of the keratin cortex thickness, being the principal factor to determine the peak wavelength of the reflectance bands; the melanosome layer only plays a minor role. The air cavity in the hollow melanosomes of the Cape starling creates a strongly enhanced refractive index contrast, thus very effectively causing a high reflectance.